Biochemical Profiling of Musa acuminata Colla (AA) ‘Kadali ’, Musa acuminata Colla (AA) Pisang lilin and Musa × paradisiaca L. (AB) ‘Kunnan’ - Silpa V. (2019)
Banana is a locally available fruit. Different varieties of banana are available locally. Knowing the nutrient composition of banana is important for including this varieties in diet. This study was designed to investigate and evaluate proximate analysis of 3 different banana varieties Musa acuminata Colla (AA) ‘Kadali’ ,Musa acuminata Colla (AA) ‘Pisang lilin’ and Musa × paradisiaca L. (AB) ‘Kunnan’. Proximate compositions of the samples were determined using the methods described in Association of Official of Analytical Chemists A.O.A.C., (1984&1995). Mineral analysis of samples were also determined using AAS (Atomic Absorption Spectroscopy). The results of proximate composition and mineral analysis are included in this dissertation.